Measuring kinetic drivers of pneumolysin pore structure. - Gilbert, R; Sonnen, A (Springer, 2016)
Most membrane attack complex-perforin/cholesterol-dependent cytolysin (MACPF/CDC) proteins are thought to form pores in target membranes by assembling into pre-pore oligomers before undergoing a pre-pore to pore transition. Assembly during pore formation is into both full rings of subunits and incomplete rings (arcs). The balance between arcs and full rings is determined by a mechanism dependent on protein concentration in which arc pores arise due to kinetic trapping of the pre-pore forms by the depletion of free protein subunits during oligomerisation. Here we describe the use of a kinetic assay to study pore formation in red blood cells by the MACPF/CDC pneumolysin from Streptococcus pneumoniae. We show that cell lysis displays two kinds of dependence on protein concentration. At lower concentrations it is dependent on the pre-pore topore transition of arc oligomers, which we show to be a cooperative process. At higher concentrations it is dependent on the amount of pneumolysin bound to the membrane and reflects the affinity of the protein for its receptor, cholesterol. A lag occurs before cell lysis begins; this is dependent on oligomerisation of pneumolysin. Kinetic dissection of cell lysis by pneumolysin demonstrates the capacity of MACPF/CDCs to generate pore-forming oligomericstructures of variable size with, most likely, different functional roles in biology.